Optimal Investment Strategies for DC Pension with Stochastic Salary under the Affine Interest Rate Model - Chubing Zhang; Ximing Rong (Discrete Dynamics in Nature and Society)
We study the optimal investment strategies of DC pension, with the stochastic interest rate (including the CIR model and the Vasicek model) and stochastic salary. In our model, the plan member is allowed to invest in a risk-free asset, a zero-coupon bond, and a single risky asset. By applying the Hamilton-Jacobi-Bellman equation, Legendre transform, and dual theory, we find the explicit solutions for the CRRA and CARA utility functions, respectively.